Availability indices of boron in major soil groups of Kerala. - Anu George (Department of Soil Science and Agricultural Chemistry,College of Horticulture, 2011)
Representative surface samples (0-20 cm) of eight soil types each from three locations (total 25 samples-including one additional sample from Kuttanad) covering nine agro-ecological units representing the major rice growing tracts of the state were collected for the present study on “Availability indices of boron in major soil groups of Kerala”. The agro-ecological units (AEU) included were Kuttanad (Kuttanad, AEU 4), Kole (Kole lands, AEU 6), Pokkali (Pokkali lands, AEU 5), Black cotton (Palakkad central plains AEU 23 and Palakkad eastern plains, AEU 10), Onattukara (Onattukara sandy plains, AEU 3), Palakkad rice soil (North central laterite, AEU 10), Laterite soils from Kozhikode, Vellanikkara and Pattambi (Midland laterite, AEU 11 and North central laterite, AEU 10)and Wayanad Plateau soils (Northern High hills, AEU 15 and Wayanad central plateau, AEU 20). The soils were characterized with respect to pH, EC, CEC, PBS and exchangeable cations, total sesquioxide and available nutrient status (Organic carbon, available B, P, K, Fe, Mn, Cu and Zn). Among the 25 soils, 15 soils showed acute boron deficiency chances (Critical limit: <0.5 mg kg-1 soil ). Fractionation of soil boron was done to separate the different forms of boron existing in soil viz. nonspecifically adsorbed plus water soluble B (NSA-B), specifically adsorbed B (SPA-B), manganese oxy-hydroxide bound B (MOH-B), B occluded in amorphous Fe-Al oxides (AMO-B), B occluded in crystalline Fe-Al oxides (CRO-B) and residual boron. Amount of boron existed in different fractions was in the following order, Residual > CRO-B > AMO-B > MOH-B > SPA-B > NSA-B. Among these fractions, MOH-B and NSA-B contributed to available B directly as well as indirectly through each other. Electrical conductivity or rather salinity is the single most important factor influencing B availability. Adsorption studies were conducted with all the soils to study the adsorption pattern of B in the above soils. The data obtained from boron adsorption experiments were fitted into different adsorption isotherms like Freundlich, Langmuir and Tempkin isotherms. 22 soils followed Freundlich adsorption pattern where as only one each of Black cotton soils (Black cotton 1) and Onattukara soils (Onattukara 2) fitted with Langmuir and Tempkin as well. Onattukara 1, the soil which recorded the lowest available B of 0.04 mg kg-1 was used to conduct a pot culture experiment using rice as test crop with three levels of B (0,10 and 20 kg ha-1) with and without 5t of FYM per hectare. The data on soil as well as plant analysis at panicle initiation and harvest stages indicated that available B status improved with increasing levels of B. Grain and total DM yield increased with the increase in boron doses without FYM. It was also noted that FYM alone could meet the B requirement. FYM with borax was found to have antagonistic effects with respect to yield as well as the nutrient contents in rice.